Pengaruh Penambahan Tepung Maizena Terhadap Daya Terima Velva Jambu Biji - Nunung Sri Mulyani (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. Guava is one type of fruit that has not received special attention in Indonesia. Guava fruit in unfavorable environmental conditions will cause damage guava fruit, both in appearance, texture, aroma and nutritional value. One way to overcome this problem is by low temperature processing such as Velva. To obtain good results Velva with a soft texture and smooth to use stabilizers with the right amount. Objective: To determine the effect of various concentrations of adding cornstarch to receive power Velva guava. This study is an experimental test using a hedonic liking organoleptic test. Conducted at the Laboratory of Food Technology Nutrition Department Banda Aceh, on the 29th until August 31, 2012 with the number of panelists somewhat trained 25 students from the Department of Nutrition Level III. The research design uses completely randomized design (CRD) non factorial, processing and analyzing data using Analysis Fingerprint Car (ANSIRA) and continued with Duncan test to see some real treatment effect. From the test results mean organoleptic guava Velva Velva acquired taste panelists are most preferred in treatment B (1%), the most preferred color Velva panelist is in treatment C (1.5%), the most preferred scents Velva panelist is on C treatment (1.5%), and the texture of the most preferred Velva panelist is in treatment B (1%). The addition of cornstarch concentration significantly affect flavor and texture, but did not significantly affect the color and aroma of guava Velva. Keywords: velva, guava, meizena